TINDAK TUTUR ILOKUSI PADA LIRIK LAGU “TARUH” KARYA NADIN AMIZAH : KAJIAN TEORI J.L. AUSTIN - Johar Amir; Ambo Dalle; Rizki Herdiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the intentions and functions of illocutionary speech acts in the lyrics of the song “Taruh” by Nadin Amizah. Language, as the primary medium of communication, does not merely function as a tool for conveying information but also serves as a means of performing communicative actions, which can be examined through a pragmatic perspective, particularly the concept of illocutionary speech acts proposed by John Langshaw Austin. This research employs a descriptive qualitative approach using pragmatic analysis. The data consist of utterances found in the song lyrics, obtained from official sources, and collected through the listening and note-taking technique.The data analysis is based on Austin’s classification of illocutionary speech acts, which includes verdictives, exercitives, commissives, behabitives, and expositives. The findings reveal that the lyrics of “Taruh” contain all five types of illocutionary speech acts with various communicative intentions and functions, namely expressing judgments, directing attitudes, affirming commitments, conveying emotions, and providing explanations. The diversity of these speech acts indicates an integrated meaning that reflects the dynamics of interpersonal relationships, trust, and the speaker’s emotional experiences. Therefore, this study confirms that song lyrics are not only aesthetic in nature but also possess communicative and reflective dimensions in representing human inner experiences.